NATO Collaborative Practices: Political and Legal Regulation - Sychova, Anastasiia (PRAWO i WIĘŹ, 2025)
This paper focuses on the dynamics of cooperative partnerships in the military and defence sector based on NATO’s strategic documents against the background of the rethinking of the global and regional security architecture, increasing hybrid threats and the trend towards strategic autonomy of national subjects. The author proposes examples of cooperative partnerships that represent the transition from multilateralism and multilateral international structures to minilateralism or multi-minilateralism by concluding bilateral agreements in the chosen vector. Ukraine is considered as an alternative model of a regional security platform through coalitions and the signing of agreements in the security dimension.